Adaptability of Yield 8lf1d its Components in Groundnut - Mothilal, A (Annals of Arid Zone, 2016)
An cxpcrimcnt was conducted over six scasons with five di fferent bunch groundnut (Arachis hypog{/('{/ L.) genotypes to evaluate them for adaptability for a wide range of characters. The genotype VRI 2 allained wider adaptability for days to 50% flowering and pod yield. The varicty TMV 2 possess stability for IDO-pod weight, IDO-kernel-weight and shelling per cent, while VRI 3 has buffering capacity for days to maturity and I~O-kernel weight. The results further suggest that crossing of VRI 2 with TMV 2 and VRI 3 will produce better genotypes with new combination of genes.